Transport consumption inequalities and redistributive effects of taxes: a repeated cross-sectional evaluation for France, Denmark and Cyprus - Berri, Akli; Vincent Lyk-Jensen, Stéphanie; Mulalic, Ismir; Zachariadis, Theodoros (My University, 2009)
Car taxes are not only a source of public revenues but also a policy tool to reduce traffic nuisances. Most car taxes were instituted in a time where the car was a luxury good (e.g. the French annual tax on vehicles owned in 1956, and the registration tax in Denmark in 1924!). The large social diffusion of the car over the past decades has doubtless lessened the progress of these taxes. The recent protests in several European countries against the rapid increase in fuel prices highlighted the sensitivity to the burden of fuel costs, not only of professionals but also of households, in particular,the suburban households who are more car-dependent. This paper evaluates transport consumption inequalities among households in Cyprus, Denmark and France, investigates their temporal dynamics and estimates the redistributive effects of taxes on different commodity categories.The paper aims at providing insights into the possibility and desirability of using fiscal levers to limit car use and its environmental nuisances. A comparative analysis is carried out in light of the differences between these countries, most notably in terms of car and fuel taxation systems and car ownership levels.